PERAN MEDIA SOSIAL DALAM DAKWAH PADA MANAJEMEN PENDIDIKAN ISLAM: PEBI JULIANTO - Julianto, Pebi (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2024)
The aim of this study is to understand how social media functions in da'wah, utilized by many preachers today, and has become a new platform for da'wah in line with the advanced development of information technology. Social media has also demonstrated its role as an advanced technological medium that can be enjoyed by people from all walks of life, anywhere, and at any time, enjoying the sophistication of current information technology. This research uses a descriptive research method, aiming to systematically describe by gathering information from various scholarly references (such as journals, theses, etc.) related to the role of social media in da'wah. In this context, the author discusses the role of social media in da'wah.